KONTRIBUSI TIMÃR LÃNG DALAM KEMAJUAN PERADABAN ISLAM PADA DINASTI TIMÃRIÃH: STUDI HISTORIS ATAS PERLUASAN WILAYAH TIMÃR LÃNG 1370-1405 M - , Deni Supriadi, Prof. Dr. M. Abdul Karim, M. A., M. A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Timûr Lâng was a Mongolian. He was the new sun from the East that had embraced Islam as his faith. As the Chengis Khan descendent, son from Chagthai, he was as strong as his grandfather. He had conquered weak regions. Initially, he defeated Tughluk Temur and Ilyas Koja, and then he fought also Amir Hussain (his brother in law). Win by win he made, and made him bravely declared as the only king of Transoxiana, the successor of Chagthai from Chengis Khan Descendant, later established Dynasty Timûriâh. The study of Islamic Civilization in the time of Dynasty Timûriâh, aimed to know the regions that had invaded by Timûr Lâng (1370-1405 M), the motive and his contribution to the civilization. To achieve the purpose, the study used some theories which are dominion theory,and invasion theory. The dominion and invasion theory were used to explain the increasing of dominion region by and his contribution to the Islamic civilization. Based on the analysis, the invasion of Timûr Lâng (1370-1405 M), covered Central Asia (Dynasty Chaghtai and Samarkhand), West Asia (Persia, Iraq (Little Asia), Turkey), and South Asia (India) also Asia-Europe (Dynasty Kipcak or Dynasty Golden Hordé). While, his contribution to the Islamic civilization included: art (language and architecture), economic, administration, politic, which an acculturation of Persian, Turkey, and Indian cultures.